Perancangan Sistem Informasi Akuntansi Persediaan Pada CV Adi Putra Utama Menggunakan Microsoft Access - Salsabila Firdaus; Zulkifli, Zulkifli; Eka Jumarni Fithri (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2024)
The purpose of this paper is to develop an inventory accounting information system at CV Adi Putra Utama using Microsoft Access. Warehouse computerization is very important for CV Adi Putra Utama to optimize inventory recording. The focus of the analysis in this final report is on the incoming and outgoing office supplies at CV Adi Putra Utama. System comparison is done by comparing the manual system currently used with the accounting information system analyzed by the author. Based on the available data, the author identified several problems, including frequent loss of inventory data because the company still uses manual methods in folio bookkeeping. The output of this design is in the form of warehouse cards, warehouse receipt and warehouse expenditure reports, and inventory reports that support CV Adi Putra Utama's business activities.